2021
DOI: 10.1016/j.xcrm.2021.100322
|View full text |Cite
|
Sign up to set email alerts
|

CD101 genetic variants modify regulatory and conventional T cell phenotypes and functions

Abstract: Highlights d Circulating immune cell frequencies are modified in individuals with CD101 variants d CD101 variants are associated with increased proinflammatory T cell function d Individuals with a particular CD101 variant have reduced Treg cell suppression capacity d CD101 contributes to regulation of inflammation at steady state

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Differential protein analysis of immature naive B cells comparing treatment-naive JDM to HC identified increased expression of CD325 and MICA-MICB and decreased expression of CD1C, BAFF-R and PD-L1 (Supplemental Table 1). Within the CD4 + T compartment (Supplemental Figure 3A), CD4 + Tregs from TNJDM had higher expression of Tim-3, ICOS, CD164 and CD38 and down-regulation of CD101, a molecule which decreases pro-inflammatory T cell responses (28). CD4 + Teff in patients with treatment-naive JDM had higher surface expression of CD164 and PD-1 and down regulation of KLRG1, an inhibitory molecule (Supplemental Figure 3B).…”
Section: Resultsmentioning
confidence: 99%
“…Differential protein analysis of immature naive B cells comparing treatment-naive JDM to HC identified increased expression of CD325 and MICA-MICB and decreased expression of CD1C, BAFF-R and PD-L1 (Supplemental Table 1). Within the CD4 + T compartment (Supplemental Figure 3A), CD4 + Tregs from TNJDM had higher expression of Tim-3, ICOS, CD164 and CD38 and down-regulation of CD101, a molecule which decreases pro-inflammatory T cell responses (28). CD4 + Teff in patients with treatment-naive JDM had higher surface expression of CD164 and PD-1 and down regulation of KLRG1, an inhibitory molecule (Supplemental Figure 3B).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, TAMs were capable of releasing various inhibitory cytokines that further impaired antitumor functions of T cells ( 6 , 39 , 40 ). Based on a functional network and literature related to CD101 ( 10 , 13 , 41 ), we found that CD101 might have a close relationship with multiple functional markers of T cells, including CD8A, CD4, CD3G, IL2, and FOXP3. Furthermore, enrichment analysis based on CD101 proteins revealed that CD101 is potentially involved in the biological processes related to T cell immune response and antigen presentation.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have demonstrated that the CD101 gene encodes a transmembrane glycoprotein predominantly expressed on dendritic cells, monocytes, and T cells ( 8 ). Of note, recent work of CD101 mainly focused on its role in restraining T cells in inflammatory processes including infectious ( 9 , 10 ) and autoimmunity diseases ( 11 , 12 ). CD101 was demonstrated to exert a potent effect on dampening T cell proliferation and activation in a TCR/CD3-dependent manner, as supported by the suppressed expression of IL-2RA and diminished secretion of IL-2 ( 8 , 13 , 14 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, given the very low levels of CD101 + CD4 T cells after infection, we are unable to sort these cells and directly assess whether they harbor more virus at this time. The idea that CD101 expression is associated with preferential infection and depletion is additionally supported by two independent studies in which genetic variants in the CD101 locus are associated with altered immune activation and increased risk of sexually acquired HIV infection [ 76 , 77 ]. While we did not find significant enrichment of HIV DNA in CD101 + cells from PBMC, we were unable to assess either LN and rectal biopsy samples for these measures, where we believe the impact of both preferential depletion of CD101 + CD4 T cells and the immunosuppressive environment created by them on ART may be most significant.…”
Section: Discussionmentioning
confidence: 99%